Leukocyte phagocytic activity in patients with rheumatoid artritis during vaccination with pneumococcal vaccine - Kostinov, M. P.; Batozhargalova, Bairma Ts; Bisheva, I. V.; Kurbatova, E. A.; Shmitko, A. D.; Lukina, G. V.; Murtazalieva, D. A.; Skhodova, S. A.; Blagovidov, D. A. (Infekt͡s︡ii͡a︡ i immunitet, 2025)
Rheumatoid arthritis (RA) is an joint autoimmune inflammatory disease characterized by systemic destructive and progressive inflammatory synovitis caused by chemokines, reactive oxygen species, and proinflammatory cytokines produced by neutrophils and macrophages in the synovial membrane. The objective of the work was to study indicators of leukocyte phagocytic activity and factors of leukocyte oxygen-dependent bactericidal activity in patients with rheumatoid arthritis receiving methotrexate (MTX) and tofacitinib (TOFA), vaccinated with pneumococcal conjugate vaccine (PCV13). Materials and methods. The study included 151 patients with RA (78.1% women and 21.9% men aged 26–69 years). PCV13 vaccination was carried out once in a dose of 0.5 ml intramuscularly in subjects receiving TOFA and MTX; TOFA was initiated 10–14 days after vaccination; those in comparison groups received same drugs. At the time of inclusion in the study, and during control visits 3 months and 12 months later, leukocyte phagocytic activity and NBT test were carried out. Results. Before the study, patients had minor quantitative and functional changes in leukocyte phagocytic activity and a decrease in the reserve capacity of oxygen-dependent bactericidal activity. In PCV13 vaccinated patients receiving TOFA (Group II), a minor decrease in the phagocytic activity of neutrophilic granulocytes was determined. In unvaccinated patients from group V receiving TOFA therapy, an increase in monocyte absorptive activity was observed both 3 months and 12 months later. In PCV13 vaccinated RA patients from group II receiving TOFA, similar changes were noted. Methotrexate therapy in PCV13 vaccinated and unvaccinated patients did not affect leukocyte phagocytic activity. Conclusion. In patients with RA, PCV13 caused a slight decrease in neutrophil absorptive capacity, which was restored one year post-vaccination accompanied by higher leukocyte oxygen-dependent bactericidal activity in the form of ROS production, which helps to strengthen immune defense in patients encountering potential pathogens.